An Effort of Hope from Hopelessness: Analysis of the Rise of Mystical Rituals such as Tarot, Fal, Magic, Amulet, Rukye - Gökdağ, Dr. Rüçhan (International Journal of Psychosocial Rehabilitation, 2020)
Humanity has always developed various rituals based on prophecies about the future in order to take measures against future problems. One of the factors underlying this choice is that two-way communication is more dominant than other rites. The effect that creates this multidirectional communication is that it is not wrong to interpret the cards, which are determined by the associations, as an opportunity to allow a cold reading of the person’s personality infrastructure. The reason that pushed the researcher into this study has been the interest shown to the tarot fortune telling, besides the fortune-telling, magic and amulet observations around him. The aim of this research is to determine the factors underlying this interest in various contexts and to present this with various population scientific data. In addition, the focus of this study is on analyzing and reflecting the internal system of the tarot deck and tradition. It was aimed to draw attention to the superiority of the cards on the hiss cold reading kart by the attentive and associative drawings of the cards and to provide a superficial view of the participants’ feelings on these cards.